Improving Student Learning Outcomes using Image Media on Learning Science Materials About Sense Tools in SDN 2 Tuksongo Students - Tri Setyorini (Universitas Sebelas Maret, 2020)
outcomes for fourth grade students of SDN 2 Tuksongo in science learning material about tools. sense. The number of students consists of 15 people. This research is an action research a class consisting of two cycles and 4 meetings. Research design following the research stage which refers to the modification of the Kemmis and Mc diagram.Taggart, namely 1) planning action, 2) executing action, 3) observation, and 4) Reflection. The data collection technique used was the teacher's observation sheet, student observation sheets, student worksheets, and student learning outcomes tests. Result research shows that there is an increase in learning outcomes, from cycle I to cycle II. This increase is evidenced by the results of the analysis of student learning outcomes tests obtained in cycle I are: students who completed 11 of 15 students or classical completeness percentage of 73.3%, 68% classical absorption, and activity students in either category. In cycle II students who completed 13 of 15 students or classical completeness 86.7%, classical absorption of 82%, and student activities are in very good category. Based on the research results indicate that The use of image media can improve the learning outcomes of fourth grade students of SDN 2 Tuksongo in science learning material about the senses.